Cash Flow, Profitability, Liquidity and Investment in Indonesia with Financial Constraint as Variable Moderating - Ibnu Damanudin; Risal Rinofah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2020)
The purpose of this study is to determine the sensitivity of cash flow, profitability, liquidity, on investments with financial constraints as moderating variables. In manufacture company food and beverage sub-sector company for the period 2015-2018. The population in this study are all food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The observation period used are 2015-2018 or 4 years. The sample is using purposive sampling method, so that a total sample of 10 samples was obtained multiplied by the observation period for 4 years to 40 research data. Data analysis technique used is multiple linear analysis method with a significant level of 5% (0.05). The results of this study indicate that cash flow and liquidity are not reflected on investments. While the profitability variable has a significant positive effect on investment. Different results are billed when cash flow and liquidity are moderated by financial constraints, cash flow and liquidity have a greater effect on non-financial constrained companies. While profitability does not have a different effect on financial constraint or unconstraint companies.